Fleet Needs Evaluation Palembang-Air Salek Route at 16 Ilir Pier Palembang City - Chairul Insani Ilham; Kodrat Alam; Fina Hamidah (IWTJ : International Water Transport Journal, 2022)
16 Ilir Pier is one of the river ports in South Sumatra Province. The Palembang-Air Salek route is one of the routes located at 16 IlirPier. The average number of trips per day on the PalembangAir Salek route is three trips. However, the operation of ships at 16 IlirPier is not matched with ideal facilities so that many ship operators suffer losses because the ships operating exceed the number of requests for transportation. The time needed to sail on the Palembang-Air Salek route is 135 minutes. This study uses several analytical methods to overcome these problems, including loading factor analysis, passenger growth prediction analysis, analysis of the need for the number of ships, and analysis of ship schedules. The results of the analysis show that the average load factor of the longboat for 15 survey days operating at 16 IlirPier is 50%, the number of ship's average departure frequency requirements for 2021 is 4 trips, Scheduling of planned longboat arrivals and departures based on service time analysis results, namely a sailing time of 135 minutes and a layover time of 84 minutes with a total of 2 ships/day. From this analysis, it is known thatthe number of longboats operating at 16 Ilir Pier carrying passengers on the Palembang-Air Salek route is not in accordance with the number of requests from service users, so a reduction must be made to the number of longboat fleets operating per day for the Palembang-Air Salek route.